Lateral asymmetry as a function of motor practice type of complex upper- and lower-limb movement in young children. Issue 3 (3rd May 2016) - Marinsek, Miha
ABSTRACT: The influence of different motor practice types on lateral asymmetry of performance was investigated in 40 preschool children. Lateral preference was measured prior the experiment. For the purpose of present study dribbling a ball with a hand and foot was used to assess lateral asymmetry of performance before and after three different motor practice types. Motor practice with the non-dominant, dominant, and both (contralateral) limbs took place in the indoor facility 4 times/week for 6 weeks. Each session lasted 30–40 min. Our results showed that unilateral practice of dribbling is more beneficial for diminishing lateral asymmetry of performance in comparison to bilateral practice. Moreover, participants who practiced with their dominant limb diminished lateral asymmetry of performance the most and made the largest overall improvement. We did not find important differences between acquisitions of dribbling with upper- and lower-extremity. In this sense, the results support the notion of lateral asymmetry of performance to be task-specific.